(untitled) (Agricultural Engineering, 2019)
The paper presents a method and results of breaking of samples that undergo elongation, printed in the FDM (Fused Deposition Modelling) technology including various height of a layer. A method of description of the FDM print was described. A developed methodology of research was presented − it was analogous to the research on breaking steel samples. The aim of the research was investigation of the height of a single layer of print on the strength parameters of the produced object. The studies on samples printed with two types of filling were made. The obtained results were set and compared. Based on the research that was carried out, it may be concluded that the tensile strength of samples made in the FDM print technology is proportional to the thickness of a single layer of print.